2002
DOI: 10.5194/acp-2-121-2002
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation coefficient of HOBr on deliquescent sodium bromide aerosol particles

Abstract: Abstract. Uptake of HOBr on sea salt aerosol, sea salt brine or ice is believed to be a key process providing a source of photolabile bromine (Br 2 ) and sustaining ozone depletion cycles in the Arctic troposphere. In the present study, uptake of HOBr on sodium bromide (NaBr) aerosol particles was investigated at an extremely low HOBr concentration of 300 cm −3 using the short-lived radioactive isotopes 83−86 Br. Under these conditions, at maximum one HOBr molecule was taken up per particle. The rate of uptake… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Diurnal patterns of BrO with maxima in the daytime have been observed [e.g., Hausmann and Platt, 1994;Saiz-Lopez et al, 2007;Pöhler et al, 2010;Liao et al, 2011a], which confirmed that BrO is a photochemically generated species with a short lifetime [e.g., Evans et al, 2003;Fan and Jacob, 1992]. BrO is the dominant bromine radical when O 3 is not severely depleted (O 3 > 1 ppbv), and observations of this species are crucial for understanding the chemical processing that leads to ODEs [e.g., Sander et al, 1997;von Glasow et al, 2002;Jones et al, 2009;Yang et al, 2010].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Diurnal patterns of BrO with maxima in the daytime have been observed [e.g., Hausmann and Platt, 1994;Saiz-Lopez et al, 2007;Pöhler et al, 2010;Liao et al, 2011a], which confirmed that BrO is a photochemically generated species with a short lifetime [e.g., Evans et al, 2003;Fan and Jacob, 1992]. BrO is the dominant bromine radical when O 3 is not severely depleted (O 3 > 1 ppbv), and observations of this species are crucial for understanding the chemical processing that leads to ODEs [e.g., Sander et al, 1997;von Glasow et al, 2002;Jones et al, 2009;Yang et al, 2010].…”
Section: Introductionmentioning
confidence: 83%
“…[17] The mass accommodation coefficient of HOBr on aerosol particles in the calculation of k a is estimated to be 0.6 [Wachsmuth et al, 2002]. The rate coefficient for reaction (R3), k 3 , is taken from a kinetics database [Sander et al, 2006].…”
Section: Steady State Calculation Of Hobrmentioning
confidence: 99%
“…Abbatt (1995) measured γ > 0.25 for HBr + HOBr in sulfuric acid solution (69 wt %) with HBr present in excess. Laboratory measurements show that HOBr reactive uptake on deliquescent NaBr and NaCl aerosol has γ > 0.2 for pH < 7 (Abbatt and Waschewsky, 1998;Fickert et al, 1999;Wachsmuth et al, 2002). Fickert et al (1999) determined the relative production of Br 2 vs. BrCl for HOBr reacting with aqueous salt solutions containing both Br − and Cl − , and found ≥ 90 % Br 2(g) production for [Br − ]/[Cl − ] ratios typical of seawater.…”
Section: Chemical Cycling Of Br Ymentioning
confidence: 99%
“…Subsequent laboratory studies have demonstrated that Reaction (R3) is efficient on saline liquid, ice, and aerosol particle surfaces (Fickert et al, 1999;Huff andAbbatt, 2000, 2002;Wachsmuth et al, 2002;Abbatt et al, 2012;Wren et al, 2013;Roberts et al, 2014). Other mechanisms of halogen activation also exist, such as the reaction of ozone with aerosol or ice-bound bromide (Oum et al, 1998;Hunt et al, 2004), but these processes are typically slower than photochemical bromine release.…”
Section: Snowpack-based Bro Events Were Common During Bromexmentioning
confidence: 99%
“…In the absence of diffusion limitations (e.g., typically for submicron particles), the rate of a heterogeneous reaction is k het = 1/4cγ SA, where c is the average velocity of the gas, and γ is the reaction probability. Wachsmuth et al (2002) indicate that heterogeneous uptake of HOBr on sea salt aerosol particles is limited by accommodation and has the value γ = 0.6. The actual value of γ may be lower because ambient particles are likely not solely sea salt.…”
Section: Aerosol Extinction Aloft Was Necessary But Not Sufficient Fomentioning
confidence: 99%